Integritas Hamba Tuhan Menurut Perjanjian Lama dan Relevansinya bagi Kredibilitas/Jati diri Hamba Tuhan Masa Kini - Sinaga, Andri Vincent (Vieka Wahana Semesta, 2024)
Servants of God with integrity are an urgent need and also everyone's desire. Integrity means there is conformity between what is said and done. In the Old Testament perspective, integrity must be possessed by all God's servants. However, in this day and age, it is difficult to find servants of God with integrity. The purpose of this research is to show that the integrity of God's servants has a big influence on the credibility or identity of God's servants (both ordained and non-ordained ministers). The methodology used is a qualitative method, with a library approach. The research results show that in the Old Testament, integrity is a reflection of a person's character. Character is formed from and as a result of a person's association with God, which results in that person possessing God's moral qualities. Integrity includes qualities in the form of inherent values such as: trustworthiness, commitment, responsibility, honesty, truth, loyalty and so on.